On the Loadstone and Magnetic Bodies - Gilbert, William; Mottelay, P. Fleury; Crew, Henry; Salvio, Alfonso de; Willis, Robert (Encyclopedia Britannica Chicago, Illinois, 1952)
On the loadstone and Magnetic Bodies and on the great magnet the Earth; By William Gilbert ; Translated by P. Fleury Mottelay
Dialogues concerning the two new sciences; By Galileo Galilei; Translated by Henry Crew and Alfonso de Salvio
An Anatomical Disquisition on the motion of the heart and blood in animals. The first anatomical disquistion on the circulation of the blood, addressed to John Riolan, A second Disquisition to John Riolan, in which many objections to the circulation of the blood are refuted. Anatomical exercises on the generation of animals; by William Harvey; Translated by Robert Willis
Includes Biographical Note
Keywords: Magnetism; Mechanics -- Early works to 1800.; Physics -- Early works to 1800.; Blood -- Circulation